Targeting Tim-3 in Cancer With Resistance to PD-1/PD-L1 Blockade - Tian, Tian; Li, Zhaoming (Frontiers in Oncology, 2021)
Programmed death receptor 1 (PD-1) or programmed death ligand 1 (PD-L1) blocking therapy has completely changed the treatment pattern of malignant tumors. It has been tested in a wide range of malignant tumors and achieved clinical success. It might be a promising cancer treatment strategy. However, one of the important disadvantages of PD-1 / PD-L1 blocking therapy is that only a few patients have a positive response to it. In addition, primary or acquired drug resistance can also lead to cancer recurrence in patients with clinical response. Therefore, it is very important to overcome the resistance of PD-1 / PD-L1 blocking therapy and improve the overall response rate of patients to the immunotherapy. T cell immunoglobulin and mucin domain molecule 3 (Tim-3) belongs to the co-inhibitory receptor family involved in immune checkpoint function. Due to adaptive resistance, the expression of Tim-3 is up-regulated in PD-1 / PD-L1 blocking therapy resistant tumors. Therefore, blocking the immune checkpoint Tim-3 might antagonize the resistance of PD-1 / PD-L1 blocking therapy. This review systematically introduces the preclinical and clinical data of combined blockade of Tim-3 and PD-1 / PD-L1 in cancer immunotherapy, and discusses the prospect of overcoming the drug resistance of PD-1 / PD-L1 blockade therapy through blockade of Tim-3.